Entrepreneurship Skills of Small and Medium Scale Poultry Farmers in Central Agricultural Zone of Nasarawa State, Nigeria - Emmanuel Suleiman Salau; Mamman Mungo Adua; Mohammed Babaiya Maimako; Janet Alanji (Journal of Agricultural Extension, 2017)
Abstract